EFFECT OF WORKING CLIMATE ON JOB SATISFACTION AND PERFORMANCE OF SECONDARY SCHOOL TEACHERS (Contemporary Journal of Social Science Review, 2024)
It has been realized in the modern era that like other organizations, educational institutions have emerged as the business organization whereas the institutions provide the supportive working environment in order to fulfill the job satisfaction for the elevation of job performance of the academicians. Establishing the relationship of working climate with job satisfaction and job performance was the major objective of this research work. The population of this study was public secondary school teachers from Hafizabad whereas, 300 respondents were selected as sample through simple random sampling technique. For data collection structured questionnaires were administered by applying survey method while for analyses of primary research data SPSS was directed to analyze the research objectives. The findings of this research indicated that the work climate had a positive and significant relationship with both job satisfaction and job performance. Further, it showed there's a significant and positive result from the work climate towards job satisfaction and job performance. This study is beneficial in strengthening secondary school education by utilizing innovative strategies.